2020
DOI: 10.1002/mgg3.1357
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants at CETP, AGER, and CYP4F2 locus with the risk of atrophic age‐related macular degeneration

Abstract: Background Age‐related macular degeneration (AMD) is the leading cause of blindness in the elderly individuals. The etiology of AMD includes environmental and genetic factors. Methods We aimed to determine the association between CETP (rs5882; rs708272; rs3764261; rs1800775; rs2303790), AGER (rs1800624; rs1800625), and CYP4F2 (rs1558139) gene polymorphisms and development of atrophic AMD. About 52 patients with atrophic AMD and 800 healthy control subjects were evaluated. The genotyping of single‐nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Besides, cytochrome P450 (CitP450) is an enzyme that plays a crucial role in the metabolism of long-chain polyunsaturated fatty acids (LCPUFAs) into epoxydocosapentaenoic acids and epoxyeicosatetraenoic acids that ultimately regulate vascular function, and it has been suggested that CitP450 monooxygenase plays a vital role in inhibiting nAMD via LCPUFA metabolites [45]. Polymorphisms in several cholesterol pathway genes including apolipoprotein E (APOE), ATP Binding Cassette Subfamily A Member 1 (ABCA1), lipase C (LIPC), Advanced Glycosylation End-Product Specific Receptor (AGER), and cholesterol ester transferase (CETP) genes have been found to be associated with the disease [46][47][48]. LIPC and ABCA1 associate with intermediate and large drusen [49].…”
Section: Dysfunction Of Proteostasis and Lipid Homeostasismentioning
confidence: 99%
“…Besides, cytochrome P450 (CitP450) is an enzyme that plays a crucial role in the metabolism of long-chain polyunsaturated fatty acids (LCPUFAs) into epoxydocosapentaenoic acids and epoxyeicosatetraenoic acids that ultimately regulate vascular function, and it has been suggested that CitP450 monooxygenase plays a vital role in inhibiting nAMD via LCPUFA metabolites [45]. Polymorphisms in several cholesterol pathway genes including apolipoprotein E (APOE), ATP Binding Cassette Subfamily A Member 1 (ABCA1), lipase C (LIPC), Advanced Glycosylation End-Product Specific Receptor (AGER), and cholesterol ester transferase (CETP) genes have been found to be associated with the disease [46][47][48]. LIPC and ABCA1 associate with intermediate and large drusen [49].…”
Section: Dysfunction Of Proteostasis and Lipid Homeostasismentioning
confidence: 99%
“…Variants in genetic loci within other regions are additional considerations when assessing risk. Particularly, gene polymorphisms related to the complement cascade (C2, C3, complement factor B [CFB], and complement factor I [CFI]) and lipid metabolism (apolipoprotein E [APOE], cholesterol ester transfer protein (CETP), and lipase C [LIPC]) modulate disease incidence and progression [ 15 , 20 , 31 , 32 , 33 ]. Summarily stated, these variants emphasize the role of local inflammatory processes in the pathogenesis of dry AMD and its progression to GA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The retina has a high metabolic activity and concentration of polyunsaturated fatty acids in photoreceptors that promotes pro-oxidative and pro-inflammatory pathways [8]. The complement pathway plays a role in the clearance of cellular debris and apoptotic cells.…”
Section: Advances In Risk Factor Classification and Positive Determin...mentioning
confidence: 99%
“…The rare variants were all found to be on or near complement genes and the protective variants were involved in complement activation and lipid metabolism [3,7]. The receptor for advanced glycation end products, involved in cascade of processes in the aging mechanism (AGER) was also found to have a higher risk of atrophic ARMD [8]. Looking at environmental, demographic, genetic, molecular and phenotypic risk factors is important to developing new treatment modalities.…”
Section: Advances In Defining Genetic Mutations Associated With Geogr...mentioning
confidence: 99%
See 1 more Smart Citation